Assessment of Strain and Strain Rate in Patients with Coronary Artery Disease Before and After Percutaneous Intervention on Left Anterior Descending Coronary Artery - Ali Heidari Sarvestani; Ahmad Separham; Naser Khezerloo (International Journal of Cardiovascular Practice, 2019)
Introduction: Strain (S) and Strain Rate (SR) as echocardiography parameters are important in assessing changes in myocardial tissue and global and regional evaluation of systolic and diastolic functions and in detection of myocardial disorders as they change in early stages of myocardial ischemia. Therefore, the aim of this study was to compare changes of S and SR indices in systolic phase in patients with a significant stenosis of left anterior descending (LAD) before and after percutaneous coronary intervention (PCI).Methods: 48 patients candidate for PCI with significant lesion in LAD were enrolled in this study. Echocardiographic images taken one day before and a week after PCI. Echocardiographic scope of the LAD was defined as mid, basal, anteroseptal and mid-septal and apical segments then, S and SR parameters in all segments measured separately during systolic phase before and after PCI and compared together.Results: there was a significant increase after PCI only in two segments and SR values showed significant increase after PCI in four segments. In the analysis of sum of mean parameters, a significant increase was observed in SR values (10.12 to 11.30; P = 0.001), but not in S values (149.54 to 143.36; P = 0.1)Conclusions: The remedial effect of PCI on deformation values was observed in the first week. In early reperfusion period, S/SR indices have potential to be used as determinants of favorable response to revascularization therapy.